Kazakhstan’s Path to Economic Diversification : Policies, Progress, and Future Directions - Murzakhalim, Aidar (2025)
This thesis examines whether – and to what extent – Kazakhstan has reduced its structural dependence on hydrocarbons since 2000 and identifies the policy levers that shape diversification. Using a 25-year annual data set (2000-2024), two complementary indicators are built: the non-oil share of GDP (NOIL) and an export-concentration index (HHI). After descriptive trend analysis, the study estimates Newey-West-robust time-series regressions in which NOIL and HHI are regressed on inward FDI, public education spending, gross fixed capital formation (GFCF), a policy-programme dummy (SPIID) and the real log oil price. Results show that a 10 percent increase in Brent crude lowers the non-oil share by roughly 0.8 percentage points and raises the HHI by about 0.11, confirming that oil-price cycles still dominate Kazakhstan’s structural outcomes. Higher GFCF is associated with a statistically significant broadening of the non-oil base and a (weaker) decline in export concentration, whereas FDI inflows, largely resource-seeking, reinforce concentration and do not expand the domestic non-oil sector. Education spending and SPIID dummies exhibit the expected signs but fall short of conventional significance thresholds. Diagnostic tests (RESET, Breusch–Godfrey, Breusch–Pagan, VIF < 3.2) validate functional form and reject serious multicollinearity, given sample length, the paper estimates HAC-robust OLS in levels and reports ADF results; cointegration tests and ECM specifications are left to future work. The thesis concludes that Kazakhstan’s infrastructure push and targeted industrial programmes have begun to offset Dutch-disease pressures, but deeper fiscal-rule reform, more selective FDI incentives and tighter human-capital alignment are required to achieve durable diversification ahead of the global energy transition.